Evaluasi dan Pemetaan Tingkat Resiko Longsor di Sumatera Selatan - Puspita Epianti; Bulkin Fathoni; Nurly Gofar (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
South Sumatra Province is situated in the southern part of Sumatra Island. The western part of this province rests on the Bukit Barisan Mountains. National roads in this area pass through steep slopes and valleys, making them prone to landslides. This study aims to evaluate the slope risk on twelve (12) national road segments crossing the Bukit Barisan area. The study was conducted based on data collected by the South Sumatra Province National Road Implementation Center (BBPJNSS) in 2018 - 2022. The risk level is calculated and classified based on the Road Slope Risk Assessment Guidelines provided by the Ministry of PUPR in 2017. The evaluation results showed that the most vulnerable road segments to landslides are Road segments 15-036, 15-37, and 15-38, connecting Lahat, Pagar Alam, Tanjung Sakti, and the border of Bengkulu Province. Meanwhile, the most prominent types of landslides are soil and rock collapse. The highest number of slopes with high and very high risks occurred in 2020; thereafter, the number declined in 2021 and 2022, as the Ministry of Public Works initiated mitigation projects in the area. The landslide risk map created in this study shows that in 2022, areas with a high risk of landslide have been reduced by the systematic mitigation program implemented by PUPR based on the slope inventory carried out since 2018.